Effects of phytonutrient-based encapsulation of Wolffia globosa on gas production, in vitro fermentation characteristics, and methane mitigation using in vitro study techniques - Uswatun Muslykhah; Srisan Phupaboon; Chaichana Suriyapha; Sukruthai Sommai; Sunisa Pongsub; Gamonmas Dagaew; Maharach Matra; Metha Wanapat (Italian Journal of Animal Science)
Microencapsulation, the advanced and newest coating technology, enhances the efficacy and stability of phytonutrients, particularly sensitive plant extracts, in animal feed. Phytonutrients have potential to mitigate methane emissions (CH4) and ammonia nitrogen (NH3-N) concentrations during rumen fermentation but require protection to maintain effectiveness. Therefore, this study evaluated the potential of duckweed powder (DWP) and microencapsulated duckweed extract (mDWE) at different levels of supplementation in an in vitro study using rumen fluid from Thai-crossbred dairy cows. Employing a 2 × 3 + 1 factorial design, the experiment tested two forms of duckweed (DWP and mDWE) at supplementation levels of 2%, 4%, and 6% + control (0%) of total dry matter substrate. Significant interactions were observed between the different forms and supplementation levels 4% mDWE (p < 0.05) notably enhanced NH3-N, total VFA (volatile fatty acid), and B. proteoclasticus, improved butyric acid (C4), Mathanobacteriales, while decreased microbial population including R. albus, R. flavefaciens and M. elsdenii and B. fibrisolvens at. mDWE increased fraction gas b, |a|+b, and cumulative gas production, dry matter (12 hours; h) and organic matter (24 h) degradability, and propionic acid (C3), while decreased CH4 production (12 and 24 h), acetate (C2) at 24 h, R. albus, R. flavefaciens, and Methanobacteriales (p < 0.05). Additionally, supplementation level significantly increased gas production kinetics and C3 (24 h), while decreased C2, C4, Methanobacteriales and CH4 production (p < 0.05). This study underscores the potential of microencapsulated duckweed extract 4% mDWE as an optimal ruminant feed additive for decreasing methane production and enhancing rumen fermentation. Further in vivo studies are recommended to validate these findings.